2021
DOI: 10.1007/s40820-021-00640-4
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Through Bottlenecks for Thermally Conductive Polymer Composites: A Perspective for Intrinsic Thermal Conductivity, Interfacial Thermal Resistance and Theoretics

Abstract: Rapid development of energy, electrical and electronic technologies has put forward higher requirements for the thermal conductivities of polymers and their composites. However, the thermal conductivity coefficient (λ) values of prepared thermally conductive polymer composites are still difficult to achieve expectations, which has become the bottleneck in the fields of thermally conductive polymer composites. Aimed at that, based on the accumulation of the previous research works by related researchers and our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 188 publications
(92 citation statements)
references
References 29 publications
0
92
0
Order By: Relevance
“…Although it was higher than that of AlN/PI thermally conductive composite films under the same amount of fillers (105 MPa), it was still significantly lower than that of the pure PI films (145 MPa). As can be seen, PI-based thermally conductive composite films prepared by the filling strategy often require the addition of a large amount of thermally conductive fillers to obtain desirable thermal conductivities, inevitably resulting in a decrease in the mechanical and processing properties, which limits their wider application. , Furthermore, studies have shown that when the λ ratio of the polymer matrix to the thermally conductive fillers is less than 0.01, it is difficult to efficiently improve the thermal conductivities of the composites by simply filling them with highly thermally conductive fillers alone, that is, novel kinds of polymer matrix with high intrinsic thermal conductivities need to be designed and fabricated. …”
Section: Introductionmentioning
confidence: 99%
“…Although it was higher than that of AlN/PI thermally conductive composite films under the same amount of fillers (105 MPa), it was still significantly lower than that of the pure PI films (145 MPa). As can be seen, PI-based thermally conductive composite films prepared by the filling strategy often require the addition of a large amount of thermally conductive fillers to obtain desirable thermal conductivities, inevitably resulting in a decrease in the mechanical and processing properties, which limits their wider application. , Furthermore, studies have shown that when the λ ratio of the polymer matrix to the thermally conductive fillers is less than 0.01, it is difficult to efficiently improve the thermal conductivities of the composites by simply filling them with highly thermally conductive fillers alone, that is, novel kinds of polymer matrix with high intrinsic thermal conductivities need to be designed and fabricated. …”
Section: Introductionmentioning
confidence: 99%
“…The development of lightness and high integration for electronics inevitably causes serious heat accumulation (> 5 W cm −2 ) [1] and electromagnetic interference (EMI), which trigger increasing demand for effective heat dissipation and EMI shielding at the multifunctional materials level [2][3][4]. In this context, polymer-based composite films integrating excellent thermal conduction and EMI shielding are expected to meet the requirement of electronics manufacturing due to their advantages of lightweight, easy processing and good designability [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…High ITR and strong phonon scattering at the interfaces (filler/filler, polymer/polymer and filler/polymer) are the main bottlenecks hindering the effective enhancement of k of thermally conductive materials [ 164 , 165 ]. When the filler loading is low, the ITR between filler and polymer matrix is the dominating factor which influences the k of composites, while when the filler network structures are formed at high loadings, the primary influencing factor turns to the ITR between filler and filler [ 166 ].…”
Section: High-performance Thermally Conductive Filmsmentioning
confidence: 99%